Planning for a payout: effectiveness of special purpose entities as state lottery administration - Fay, Daniel L. (2016)
Public management literature has previously examined privatization in which government contracts with private firms or other organizations to provide goods or services to the public. However, privatization of organizational structure through the creation of special purpose organizations remains relatively underexplored. This study examines the policy consequences of privatizing state lottery organizations by comparing the revenue returned to state governments from lotteries managed by independent state agencies to lotteries managed by privatized special purpose organizations. Using data on the organizational structure and revenue returns of the state lottery administrations in the United States from 1985-2008, fixed effects analyses demonstrate that independent state lottery agencies are more effective than privatized special purpose administrations. The revenue costs of lottery administrative privatization are robust to multiple measurements and specifications, and suggest that choosing a privatized organizational structure can cost states tens of millions of dollars in lost lottery revenue annually. Special purpose lottery administrations maximize returns to state governments in average-sized states with low African American populations. State-agency lottery administrations maximize returns to state governments in small- or large-sized states with high per capita income and high population density. Implications of state special purpose administrations and future research opportunities are discussed.
Keywords: Privatization; Lotteries